The Pyramid of Consciousness: A Conceptual Model for Artificial Consciousness and Human– Artificial Intelligence Hybrid Integration - Ruiz-Vanoye, Jorge A.; Díaz-Parra, Ocotlán; Trejo-Macotela, Francisco R.; Simancas-Acevedo, Eric; Zarazúa Silva, Juvencio S.; Salas López, Julio C. (International Journal of Combinatorial Optimization Problems and Informatics, 2025)
This paper examines the continuum from natural to artificial consciousness, highlighting the biological basis of subjective experience. It introduces synthetic consciousness as a hybrid of neural and algorithmic systems and examines ethical, legal, and ontological implications of human–AI integration. The Pyramid of Consciousness framework guides reflection on autonomy, identity, and the shifting boundary between organic cognition and intelligent machines. Smart citations: https://scite.ai/reports/10.61467/2007.1558.2025.v16i4.1184